Recent developments in reliability-based civil engineering - Haldar, Achintya (World Scientific, 2006)
Authored by the most active scholars in their respective areas, this volume covers the most recent developments, both theoretical and applicative, in structural reliability evaluation areas, many of which are cutting-edge and not discussed elsewhere in book form. The broad coverage includes the latest thoughts on design for low probability and high consequence events like the failure of the World Trade Center as well as risk acceptability based on the Life Quality Index. Other chapters discuss the development of the performance-based design concept, and the generally overlooked area of the reliability evaluation of bridges and offshore structures. Since the finite element method is routinely used for structural analyses, emphasis is put on discussing reliability evaluation using finite elements including consideration of the mesh-free finite element method. Corrosion and fatigue reliability evaluation techniques are other urgent issues that are dealt with in depth. Among the many additional included topics, a chapter is devoted to health assessment of existing structures, currently the most active research area.